The Use of the Rasch Model to Analyze Misconceptions on the Topic of Integer Numbers - Jeranah; Nisraeni; Rezki Novianti; Nuril Huda; Asdar Ahmad (Universitas Pendidikan Ganesha, 2025)
Students still experience difficulties and many misconceptions about mathematical concepts, especially integer operations. The urgency of the research is based on the fact that these misconceptions can affect the development of students' understanding in mathematics. The aim is to identify and analyse students' errors and misconceptions using the Rasch Model. The research method used is quantitative with a survey approach, with respondents of 675 elementary and high school students in Makassar. Data were collected through instruments, multiple-choice questions arranged according to mathematics curriculum standards, then analysed using the Rasch Model to identify the type of misconception and the level of difficulty of the questions. The results show that the main misconceptions are related to the understanding of negative symbols and the concept of numerical balance. These findings indicate the need to develop more comprehensive diagnostic instruments and improve teacher training in integer learning. In conclusion, the use of the Rasch Model has proven effective in identifying misconceptions and can be the basis for developing learning strategies. The implications of the research support teacher training and methods for learning mathematical concepts.